Pelaksanaan kegiatan ekstrakurikuler pramuka dalam mengembangkan karakter disiplin siswa - Karina Karina; M. Ismail; Jumrawati Jumrawati (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the implementation of Scout extracurricular activities in developing students’ disciplinary character at SMAN 2 Mataram and to identify the supporting and inhibiting factors. Discipline is an important character value that shapes responsibility, rule compliance, and orderliness in daily life. This research uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving Scout coaches, vice principal of student affairs, and students as informants. Data analysis uses the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results show that Scout extracurricular activities are implemented systematically through routine training, marching exercises, ceremonies, and camping activities. These activities contribute to developing discipline through punctuality, rule compliance, responsibility, and teamwork. Supporting factors include student enthusiasm, school support, and coach competence, while inhibiting factors include uneven motivation and scheduling conflicts. Thus, Scout activities are effective in developing students’ disciplinary character.